Targeting DNA Minor Groove by Hybrid Molecules as Anticancer Agents - Nekkanti, Shalini; Tokala, Ramya; Shankaraiah, Nagula (Current Medicinal Chemistry, 2017)
Agents which can recognize and bind specific sequences of DNA offer selective therapy through the modulation of specific transcription factors or genes. Recently, there has been renewed interest in the field of anticancer minor groove binders. This may be attributed to the fact that many compounds of this class have demonstrated significant antitumor activity against a wide variety of cancers in recent clinical trials. This review will discuss the recent to overcome the drawbacks of existing minor groove binding anticancer agents through raeffortstional drug design based on scaffolds with known antitumor activity.
Keywords: pyrrolo[2